2010
DOI: 10.1063/1.3428622
|View full text |Cite
|
Sign up to set email alerts
|

Communications: A rigorous transition state based approach to state-specific reaction dynamics: Full-dimensional calculations for H+CH4→H2+CH3

Abstract: Communication: Ro-vibrational control of chemical reactivity in H+CH 4 → H 2 +CH 3 : Full-dimensional quantum dynamics calculations and a sudden model

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 38 publications
1
45
0
Order By: Relevance
“…The previous work 24,25 demonstrated that the quantum transition state concept permits the calculation of initial state-selected (J = 0) reaction probabilities for the H + CH 4 → H 2 + CH 3 reaction in full dimensionality. Using the scheme presented, these calculations could now be extended to also compute state-to-state reaction probabilities for this system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous work 24,25 demonstrated that the quantum transition state concept permits the calculation of initial state-selected (J = 0) reaction probabilities for the H + CH 4 → H 2 + CH 3 reaction in full dimensionality. Using the scheme presented, these calculations could now be extended to also compute state-to-state reaction probabilities for this system.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate full-dimensional quantum dynamics calculations for six atom reactions have up to now only been presented for cumulative reaction probabilities and thermal rate constants [14][15][16][17][18][19][20][21][22][23] or initial state-selected reaction probabilities 24,25 and studied the H + CH 4 → H 2 + CH 3 , [14][15][16][17][18][19][22][23][24][25] [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and propagated wave packets representing vibrational states of the activated complex which have been a) Electronic mail: rwelsch@uni-bielefeld.de. b) Electronic mail: uwe.manthe@uni-bielefeld.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, just recently MCTDH calculations propagating wave packets from the transition state to the asymptotic region obtained initial state-selected reac- [6,7]. Based on older ideas [43,134,135], these calculations utilized the quantum transition concept to calculate state-specific quantities observed in scattering experiments and provided a perspective towards an accurate and fully state-resolved description of polyatomic reactions as H + CH 4 , Cl + CH 4 , or F + CH 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, rigorous reaction rate calculations have a pioneering role in the quest towards the accurate description of increasing complex reactions. Besides the focus on selected observables as reaction rates [2,5] or initial state-selected reaction probabilities [3,4,6,7] (the first full-dimensional quantum dynamics calculation of initial state-selected reaction probabilities for a six atom reaction appeared just recently [6,7]), the development of efficient schemes for the multi-dimensional wave packet propagation, particularly the multi-configurational time-dependent Hartree (MCTDH) approach [8,9], contributed significantly to the progress. Thermal rate constants are generally the magnitudes most relevant for a chemist investigating a reaction.…”
mentioning
confidence: 99%
“…Fulldimensional calculations of systems of this size have mainly been performed for reactions with a single heavy atom. [16][17][18][19] The present reaction has three heavy atoms, which leads to a significant increase in the computational cost for the quantum dynamics due to an increase in the number of basis functions or grid points, and such calculations are therefore still rare, especially for state-selected properties. [20,21] In addition, the Cl − + P H 2 Cl → ClP H 2 + Cl − reaction proceeds through a transition complex well instead of a transition state barrier.…”
Section: Introductionmentioning
confidence: 99%